Early Experience With Virtual and Synchronized Augmented Reality Platform for Preoperative Planning and Intraoperative Navigation: A Case Series. Issue 4 (25th June 2021) - Louis, Robert G; Steinberg, Gary K; Duma, Christopher; Britz, Gavin; Mehta, Vivek; Pace, Jonathan; Selman, Warren; Jean, Walter C
Abstract: BACKGROUND: Virtual reality (VR) allows for presurgical planning. Intraoperatively, augmented reality (AR) enables integration of segmented anatomic information with neuronavigation into the microsurgical scene to provide guidance without workflow disruption. Combining VR and AR solutions may help guide microsurgical technique to improve safety, efficiency, and ergonomics. OBJECTIVE: To describe a VR/AR platform that provides VR planning and intraoperative guidance via microscope ocular injection of a comprehensive AR overlay of patient-specific 360°/3D anatomic model aligned and synchronized with neuronavigation. METHODS: Custom 360° models from preoperative imaging of 49 patients were utilized for preoperative planning using a VR-based surgical rehearsal platform. Each model was imported to SyncAR, the platform's intraoperative counterpart, which was coregistered with Medtronic StealthStation S8 and Zeiss or Leica microscope. The model was injected into the microscope oculars and referenced throughout by adjusting overlay opacity. For anatomic shifts or misalignment, the overlay was reregistered via manual realignment with known landmarks. RESULTS: No SyncAR-related complications occurred. SyncAR contributed positively to the 3D understanding of patient-specific anatomy and ability to operate. Preoperative planning and intraoperative AR with 360° models allowed for more precise craniotomy planning and execution. SyncAR was useful for guiding dissection, identifying critical structures including hidden anatomy, understanding regional anatomy, and facilitating resection. Manual realignment was performed in 48/49 surgeries. Gross total resection was achieved in 34/40 surgeries. All aneurysm clipping and microvascular decompression procedures were completed without complications. CONCLUSION: SyncAR combined with VR planning has potential to enhance surgical performance by providing critical information in a user-friendly, continuously available, heads-up display format.